Helminth-Tuberculosis Co-infection: An Immunologic Perspective. Issue 9 (September 2016) - Babu, Subash; Nutman, Thomas B.
Abstract : Over 2 billion people worldwide are infected with helminths (worms). Similarly, infection with Mycobacterium tuberculosis (Mtb) occurs in over a third of the world's population, often with a great degree of geographical overlap with helminth infection. Interestingly, the responses induced by the extracellular helminths and those induced by the intracellular Mtb are often mutually antagonistic and, as a consequence, can result in impaired (or cross-regulated) host responses to either of the infecting pathogens. In this review, we outline the nature of the immune responses induced by infections with helminths and tuberculosis (TB) and then provide data from both experimental models and human studies that illustrate how the immune response engendered by helminth parasites modulates Mtb-specific responses in helminth–TB coinfection Trends: Helminths appear to influence the immune response to tuberculosis (TB) by modulating both innate and adaptive responses to the TB pathogen. T cells are the predominant cell type studied in the context of helminth–TB coinfections and appear to exhibit both dampened effector responses and expanded regulatory responses. Amongst the various regulatory mechanisms examined, IL-10 appears to play the most profound role in influencing the T cell responses to mycobacterial antigens in the context of helminth–TB coinfection. Mechanistic studies examining the mechanism by which helminths influence pathogenesis or pathology in active TB are currently ongoing.